2016
DOI: 10.1099/jgv.0.000608
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus resistance to broadly neutralizing antibodies measured using replication-competent virus and pseudoparticles

Abstract: A better understanding of natural variation in neutralization resistance and fitness of diverse hepatitis C virus (HCV) envelope (E1E2) variants will be critical to guide rational development of an HCV vaccine. This work has been hindered by inadequate genetic diversity in viral panels and by a lack of standardization of HCV entry assays. Neutralization assays generally use lentiviral pseudoparticles expressing HCV envelope proteins (HCVpp) or chimeric full-length viruses that are replication competent in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 60 publications
1
38
0
Order By: Relevance
“…Direct comparison of the data acquired using the J6 HCVpp and J6/JFH HCVcc indicates excellent agreement (R 2 = 0.96, S3 Fig. ); this further demonstrates that HCVpp are a good model for HCV entry [56].…”
Section: Hcv Receptor Activitymentioning
confidence: 63%
“…Direct comparison of the data acquired using the J6 HCVpp and J6/JFH HCVcc indicates excellent agreement (R 2 = 0.96, S3 Fig. ); this further demonstrates that HCVpp are a good model for HCV entry [56].…”
Section: Hcv Receptor Activitymentioning
confidence: 63%
“…6). Experimental neutralization of 1a53 HCVcc exceeded Loewe-predicted neutralization at 7 of 10 concentrations (P < 0.05 for each), while it differed from Bliss-predicted virus (22,24). Experimental neutralization of strain 1a53 HCVpp significantly exceeded the neutralization predicted by the Loewe additivity model at six of nine concentrations (P < 0.05 for each), while it differed significantly from the Bliss prediction at only two of nine concentrations.…”
Section: Hepc74/hepc98 Neutralization Is Synergistic Relative To the mentioning
confidence: 76%
“…1A and Table S1). We analyzed the neutralizing breadth of each of these NAbs in prior studies using a diverse panel of 19 genotype 1 HCVpp (20,(22)(23)(24). We previously showed that these quantitative neutralization data across diverse strains comprise a neutralization profile for each NAb, which can be compared among NAbs to understand functional relationships (22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations